Association of Dietary Factors With Grip Strength, Body Fat, and Prevalence of Sarcopenic Obesity in Rural Korean Elderly With Cardiometabolic Multimorbidity - Kim, Jieun; Baek, Younghwa; Jeong, Kyoungsik; Lee, Siwoo (Frontiers in Nutrition, 2022)
Background and aims: Aging accompanied by cardiometabolic multimorbidity (CM) promotes chronic low-grade inflammation, increased oxidative stress, and insulin resistance, which result in loss of muscle mass and functional impairment. Better quality diets have been directly associated with health status and decreased risk of all-cause mortality; however, no study has investigated the relationship of dietary factors with grip strength, body composition, and prevalence of sarcopenic obesity (SO) in Korean rural residents according to their CM pattern. Therefore, we aimed to examine this association among this population. Methods: This cross-sectional study utilized data from 932 rural residents aged ≥65 years. An exploratory tetrachoric factor analysis revealed four multimorbidity patterns: CM, inflammatory disease, respiratory disease, and cancer and other diseases; all participants were categorized into the CM and non-CM groups. Skeletal muscle mass and the prevalence of sarcopenia were estimated using bioelectrical impedance analysis. Dietary assessment was analyzed using a validated 106-item food frequency questionnaire. Adjusted multiple linear regression and multivariate logistic regression were employed to examine the association of dietary factors with muscle strength, quality, and SO prevalence ratio in elderly participants. Results: The mean age of the participants was 71.8±0.1 years (65.8% women). Dietary fat and protein intake were positively correlated with handgrip strength in women with CM, after adjusting for covariates (p=0.001). Similarly, protein intake (g/kg) was positively associated with appendicular skeletal muscle mass (ASM) (kg/m2) and ASM (%) in both sexes in the CM and non-CM groups. Regarding the tertiles of wheat intake (g/d), 2.1-fold increase in SO prevalence ratios (PR: 2.149, CIs: 1.134–4.071) was observed in the highest tertile (T3: 269.1 g/d), compared to the lowest tertile (Q1: 8.6 g/d) in the CM group. Higher tertile of meat intake (T2: 34.8 g/d, T3: 99.5 g/d) had a 2-fold increase in SO (PR: 1.932, CIs: 1.066–3.500) compared to the lowest tertile (T1: 9.2 g/d) in the CM group. Conclusions: Overconsumption of wheat and meat negatively impacted the development of SO, while protein intake was positively associated with grip strength and skeletal muscle mass in elderly Koreans with CM.